2018
DOI: 10.1038/s41467-018-05232-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient RNA-guided base editing in rabbit

Abstract: Cytidine base editors (CBEs) and adenine base editors (ABEs), composed of a cytidine deaminase or an evolved adenine deaminase fused to Cas9 nickase, enable the conversion of C·G to T·A or A·T to G·C base pair in organisms, respectively. Here, we show that BE3 and ABE7.10 systems can achieve a targeted mutation efficiency of 53–88% and 44–100%, respectively, in both blastocysts and Founder (F0) rabbits. Meanwhile, this strategy can be used to precisely mimic human pathologies by efficiently inducing nonsense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 42 publications
5
122
0
2
Order By: Relevance
“…Therefore, the base editing windows for ABEs and CBEs at some target sites in our study (Table ) are larger than previously defined in mammalian systems (Gaudelli et al ., ; Komor et al ., ). Two recent in vivo base editing studies in mouse and rabbit also showed that ABEs and CBEs with SpCas9 can edit target adenines and cytosines outside of the canonical base editing activity windows at some target sites (Liu et al ., ,b). As the base editing windows characterized in previous studies were derived from limited target sites and were mainly from cell‐based assays which had relatively a short time for base editors to function (Gaudelli et al ., ; Komor et al ., ), more target sites need to be tested, and in vivo base editing studies are required to accurately define the base editing windows for both adenine and cytosine base editors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the base editing windows for ABEs and CBEs at some target sites in our study (Table ) are larger than previously defined in mammalian systems (Gaudelli et al ., ; Komor et al ., ). Two recent in vivo base editing studies in mouse and rabbit also showed that ABEs and CBEs with SpCas9 can edit target adenines and cytosines outside of the canonical base editing activity windows at some target sites (Liu et al ., ,b). As the base editing windows characterized in previous studies were derived from limited target sites and were mainly from cell‐based assays which had relatively a short time for base editors to function (Gaudelli et al ., ; Komor et al ., ), more target sites need to be tested, and in vivo base editing studies are required to accurately define the base editing windows for both adenine and cytosine base editors.…”
Section: Resultsmentioning
confidence: 99%
“…However, for the majority of targets, the editing efficiencies were lower than 20%, which were not as high as those obtained in eukaryotes, such as approximately 50% in human cells (Gaudelli et al, 2017) and 44 to 100% in rabbits (Z. Liu et al, 2018). In nature, adenosine deaminase mediates deamination of adenosine (A) in RNA into inosine (I).…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of these tools in X. tropicalis remains to be tested. 26 (2) numbers are shown on the left side. Genotype frequencies are shown on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, base editor 3 (BE3), a fusion of a clustered regularly interspaced short palindromic repeat-associated protein 9 (Cas9) nickase, a cytidine deaminase [rat apolipoprotein B mRNA editing enzyme catalytic subunit 1 (APOBEC1)], and the uracil DNA glycosylase inhibitor (UGI), has been developed as a base editor (BE3), which efficiently induces the C-G pair to T-A pair transition in living human cells without inducing double-stranded DNA breaks (17). Subsequent studies demonstrated the effectiveness of this base editing strategy in yeasts, plants, and various animal models (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Its application in X. tropicalis remains to be tested.…”
mentioning
confidence: 99%